Effect of umbelliferone on adjuvant-induced arthritis in rats by MAPK/NF-κB pathway - Ouyang L (Drug Design, Development and Therapy, 2019)
Liu Ouyang, Yang Dan, Zengwu Shao, Shuhua Yang, Cao Yang, Guohui Liu, Wu Zhou, Deyu Duan Department of Orthopaedics, Union Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan 430022, People’s Republic of China Purpose: Umbelliferone (Umb), a member of coumarin family, is found in many plants and is a promising molecule with potential anti-inflammatory, anti-oxidative, and anti-tumor activities. However, the effect of Umb on arthritis remains unclear.Methods: A rat model with Freund’s complete adjuvant (FCA)-induced arthritis was developed and used to test the efficacy of Umb on arthritis rats. Rats were given an intragastric injection of Umb (20 and 40 mg/kg) once daily from days 21 to 28 after the administration of FCA. Hind paw volume was assessed using a volume meter. The pro-inflammatory cytokine levels and prostaglandin E2 (PEG2) level in serum and synovial fluid were detected by ELISA. HE staining was used to determine representative histological changes in joint tissues, and Western blot analysis was employed to study the effects of Umb on MAPK/NF-κB signaling pathway.Results: Our results showed that Umb suppressed the release of IL-6, IL-1β, tumor necrosis factor-alpha, and PEG2. In addition, Umb could also dramatically ameliorate the pathological changes observed in rat joints. Based on the results of Western blot, we also observed that Umb could strikingly suppress the expression of MAPK/NF-κB pathway molecules.Conclusion: These results proved that treatment with Umb is very effective for arthritis and inhibiting the MAPK/NF-κB signaling pathway may be a potential therapeutic target for treatment of arthritis. Keywords: umbelliferone, arthritis, inflammation, MAPK/NF-κB pathway